(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the economic and social effects of minimum wage policy from both theoretical and practical perspectives. The minimum wage is considered a key economic instrument that directly affects labor market equilibrium, employment levels, household incomes, and poverty reduction. The study evaluates the impact of minimum wage adjustments on employment, labor supply, productivity, and income inequality based on different economic approaches. In addition, the role of minimum wage policy in promoting social justice, improving living standards, and strengthening social stability is examined. The findings highlight the potential of an effective minimum wage policy to balance economic efficiency and social equity.